Indications and endoscopic findings of upper gastrointestinal diseases in Africa: A systematic review & meta-analysis. - Seid Mohammed Abdu; Ebrahim Msaye Assefa; Hussen Abdu (PLoS ONE)
Background Upper gastrointestinal endoscopy (UGIE) plays a crucial role in diagnosis of gastrointestinal pathology. Therefore, this systematic review and meta-analysis aimed to assess the indications and findings UGIE, while exploring their regional distribution and temporal trend across Africa. Methods Systematic Reviews and Meta-Analysis of pooled prevalence for various indications and endoscopic findings were analyzed from multiple studies in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Results Seventeen common indication were identified. Of these dyspepsia was the most prevalent indication 52.4%, followed by abdominal pain 17.4%, hematemesis 13.9%, and GERD symptoms 11.2%. Other indications included dysphagia 9.2%, vomiting 9.2, odynophagia 3.5%, and melena 6.2% were identified. Rare indications such as anemia 2.3%, weight loss 2.6% were also reported. Regarding endoscopic findings, thirty-one common findings were identified by UGIE. Gastritis (33.3%) was the most common findings followed by normal findings 21.8%, the third most common was PUD 15.1%, particularly duodenal ulcer (10%), gastric cancer 3.3% were also prevalent in stomach. Related to esophageal findings, GERD 9.6%, esophagitis 8.3%, esophageal varices 7.2% and esophageal cancer 6.1% were identified. Regional difference were apparent, with esophageal cancer prevalent in Eastern (10%) and Southern Africa (10%). Gastritis (45%) and GERD (18%) were more apparent and common in Northern Africa. Even though it is not significant, temporal trends showed an increase in prevalence of gastritis (26 to 36%) and esophagitis (6 to 10%) from 2000-2010 to 2011-2024. Conclusion Most UGIE indications resulted significant UGIT pathology. However, this analysis did not assess age, sex based indications and findings and their relationship among specific indications and UGIE findings. So, future analysis should focus on age and sex based difference in indications and findings, and explore their relationship among specific indication and corresponding UGIE findings.